2021
DOI: 10.1002/jcla.23785
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated circ_0004913, circ_0008160, circ_0000517, and their potential as biomarkers for disease monitoring and prognosis in hepatocellular carcinoma

Abstract: Objective: Circular RNA_0004913 (circ_0004913), circular RNA_0008160 (circ_0008160), and circular RNA_0000517 (circ_0000517) are shown to be dysregulated in HCC tissues and cell lines, and also show potential in regulating hepatocellular carcinoma (HCC) pathogenesis. This current study attempted to find possible associations of circ_0004913, circ_0008160, and circ_0000517 with clinical features and prognosis of HCC patients.Methods: A hundred and fifty HCC patients who received hepatectomy were retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…With the continuous deepening of the research, we have found that circRNA is closely related to the occurrence and development of a variety of cancers, which further suggests that it is expected to become a new biomarker and therapeutic target. 12 , 13 In this study, we identified that the expression of circCORO1C in HCC tissues and cells was abnormally increased. In addition, in vivo and in vitro functional experiments have proved that high expression of circCORO1C can promote the malignant phenotype of HCC.…”
Section: Discussionmentioning
confidence: 75%
“…With the continuous deepening of the research, we have found that circRNA is closely related to the occurrence and development of a variety of cancers, which further suggests that it is expected to become a new biomarker and therapeutic target. 12 , 13 In this study, we identified that the expression of circCORO1C in HCC tissues and cells was abnormally increased. In addition, in vivo and in vitro functional experiments have proved that high expression of circCORO1C can promote the malignant phenotype of HCC.…”
Section: Discussionmentioning
confidence: 75%
“…Li’s study investigated 150 HCC patient tissues after surgery and found circ_0004913 and circ_0008160 to be down-regulated but circ_0000517 up-regulated in HCC tissue. Further studies found that increased expression of circ_0004913 is negatively related to largest tumor size and correlated with longer OS and that it might act as a monitoring and prognostic biomarker for HCC ( 116 ). Therefore, a single circRNA has been demonstrated to have excellent performance in HCC diagnosis and prognosis, yet the combination of several circRNAs performs significantly better.…”
Section: Novel Implications Of Circrna In Hccmentioning
confidence: 99%
“… 21 Another study presented that circ_0004913 was dysregulated during HCC progression and the alteration of circ_0004913 could be used as an evaluation factor for HCC severity and prognosis. 22 Liu et al demonstrated the down‐regulation of circ_5692 in HCC tissues and cells, and circ_5692 overexpression inhibited malignance of HCC cells and the tumour growth of HCC xenograft mouse model. 23 …”
Section: Discussionmentioning
confidence: 99%